Dissolution of theophylline from extended-release tablets under cyclic retrograde peristaltic contractions in the Dynamic Colon Model - Connor O'Farrell; Konstantinos Stamatopoulos; Mark J. H. Simmons; Hannah Batchelor (University of Huddersfield Press, 2022)
The dynamic colon model isa biorelevant in vitro model of the human proximal colon. In vivo, the large intestine mixes its contents using peristaltic waves that propagate both forwards(antegrade) and backwards (retrograde). This work studies the dissolution profile of theophylline from Uniphyllin Continus 200 mg prolonged release tablets and the distribution of dissolved theophylline in viscosity-enhanced media under the influence of a cyclic retrograde peristaltic contraction. At 16-and 24-hours, and theophylline dissolved from the tablet and the fluid inside the mimic intestinal system approached homogeneity.